Defining Features of Protective CD4 T cell responses to Mycobacterium tuberculosis - Sakai, Shunsuke (2014)
CD4 T cells are critical for control of Mycobacterium tuberculosis (Mtb) infection and represent the best hope for vaccine-elicited protection. However, little is understood about the properties of Mtb-specific CD4 T cells that mediate control, and the lack of correlates of protection present a significant barrier to the rational development of new vaccination and therapeutic strategies which are sorely needed. Here we discuss the features of protective CD4 T cells including recent evidence for IFN-γ dependent and independent mechanisms of protection, poor protection by terminally differentiated cells and the importance of T cell migratory capacity for the control of Mtb infection.